[BP.11.01] THE ESH SUMMER SCHOOL EXPERIENCE: A DESCRIPTIVE ANALYSIS. (September 2017) - Guerrot, D.; Kantauskaite, M.; Teeaar, T.; Silva, C. Santos; Hoffmann-petersen, N.; Nguyen, T.; Humalda, J.
Abstract : Objective: The first ESH Summer School was organized in Berlin in 1999. A course has been held every year since then, with the main goal of creating a hypertension network among young European and non-European fellows, who represent the next generation of hypertension specialists, to facilitate collaborative hypertension research around the world. The objective of the present work was to describe the characteristics of the ESH Summer School participants at the time of their participation, and at the latest follow-up. Design and method: We retrospectively recorded data from former ESH Summer School participants, from 5 different Summer Schools. Data were collected via an questionnaire sent by email, and subsequently anonymized. Results: 72 ESH Summer School participants were included, from 29 different countries. The 3 most frequently represented countries were Belgium, Denmark, and Italy. At the time of the Summer School, 72% of participants worked in a university hospital and 22% in a general hospital. Cardiology was the main medical speciality of participants (41%), followed by internal medicine (24%), and nephrology (17%). At follow-up, the mean percentage of activity time dedicated to hypertension was 36 ± 24%. Former participants had regular membership in national hypertension societies in 75% cases and ESH membership in 28% cases. Persistent interactions with other ESH Summer School participants were reported by 47% of participants at follow-up. Between the Summer School and follow-up, the mean number of Pubmed published articles of participants increased from 6 ± 7 to 23 ± 21. Conclusions: The ESH Summer School provides a unique opportunity for young physicians involved in hypertension to receive high-level education by international leaders in the field. This study shows that the ESH Summer School succeeds in encouraging long-lasting international networks between former participants, and therefore contributes to the excellence of research and clinical care in hypertension.